2016
DOI: 10.5120/ijca2016911170
|View full text |Cite
|
Sign up to set email alerts
|

Various Techniques for Classification and Segmentation of Cervical Cell Images - A Review

Abstract: Pap smear test plays an important role for the early diagnosis of cervical cancer in which human cells taken from the cervix of patient are analysed for pre-cancerous changes. The manual analysis of these cells by expert cytologist is labor intensive and time consuming job. The automatic and accurate detection of cervical cells are two critical preprocessing steps for automatic Pap smear image analysis and also for diagnosis of pre-cancerous changes in the uterine cervix. Similarly, the reliable segmentation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The patch-based sorting allowed for the calculation of the central value. According to Sharma and Mangat [13], an additional improvement was made to the work, the author improved the "fuzzy c-means (FCM)" clustering technique by working with various numbers of clusters rather of just one. This was done in order to reinforce the clustering of the data.…”
Section: Literature Surveymentioning
confidence: 99%
“…The patch-based sorting allowed for the calculation of the central value. According to Sharma and Mangat [13], an additional improvement was made to the work, the author improved the "fuzzy c-means (FCM)" clustering technique by working with various numbers of clusters rather of just one. This was done in order to reinforce the clustering of the data.…”
Section: Literature Surveymentioning
confidence: 99%
“…[107] B. Sharma et al propose an idea of integrating segmentation methods with the region of interest locating methods to improve the segmentation and classification accuracy and achieve an accuracy of 93.7 % with Herlev dataset [108] D. A. Clausi et al use Gray Level Co-occurrence Probabilities (GLCP) for segmenting images and concluded that the GLCPs are more sensitive to texture boundary which results in good classification accuracy. [109] W William et al present a review on image analysis and machine learning techniques for automated cervical cancer screening and identified K-nearest-neighbors and support vector machines algorithms as an excellent classifiers for cervical image with an accuracies of over 99.27% and 98.5% respectively for 2class classification problem.…”
Section: Classification Performancementioning
confidence: 99%
“…While automation-assisted reading systems can increase productivity by reducing the time needed to read slides, their current performance and costs are not recommended for application in primary cervical screening [11,12]. To this end, lots of automation-assisted methods based on cervical cell image analysis have been proposed [5,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%